Georgia Architectural and Historic Properties Survey of Simpson St., Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Simpson St., Sycamore, Turner County, Ga., 1981. One and a half story Georgian plan house with pyramidal hipped roof with pedimented gables, and one hipped dormer. Hipped porch supported by Tuscan order columns. Shiplap siding. Double sash windows with 1/1 and 4/4 leaded glass lights. Interior chimneys. Transom over front door. Brick piers. Bays on right front and left side elevations. Fair condition. "V.B.D. - 102 - between blocks 9 & 10, unopen portion of Simpson St." Date of Construction: c. 1908. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Simpson St., Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 54.5 MB (57,224,878 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)